Permeability determination of hydrate sediments and a new reduction model considering hydrate growth habit - Shen, Pengfei; Li, Xiaosen; Li, Zhenhe; Li, Gang (Fuel, 2020)
The saturation (SH) and growth habit of hydrates in sediments directly affect the evaluation of permeability. This work was devoted to evaluating the growth habit of hydrates in sediments by permeability measurements. The water effective permeability of hydrate sediments with different SH was obtained, and these permeability data were excellent in stability and accuracy. The change of differential pressure of hydrate sediments with water injection was completely recorded, it was a new found that the differential pressure was unstable in the first few minutes, and it is not recommended to employ short-term data to evaluate the permeability of the hydrate sediments. Based on the hypothesis of wedge tetrahedral filling of sediment particles, the growth habits of hydrates were compered in the models of hydrate coating grain and occupying pore center respectively. By analyzing the experimental data with the reduction models in different hydrate growth habits, it was founded that the hydrates were more likely to form in the pore centers rather than coating grains. Finally, the ratio of the internal surface area of pore space with and without hydrate was simplified to an expression related to S-H in a new model of water relative permeability. This model could distinguish the growth habits of hydrate in porous media and provide a more accurate prediction of water relative permeability.